Applying Techniques in Creative Writing by EFL Students - Rebin Abdulqader; Saifadin Ibrahim Sharif; Saman Ahmad Abdulla (Zanco Journal of Humanity Sciences)
In this research, the aim was to find out the impact of literary devices used by college students in creative writing. More than 60 participants were enrolled. Quantitatively, it was found that creative writing skills can be boosted especially through the use of literary devices that are crucial for improving students' performances in writing. The respondent took the creative writing course and signed up for two exams. Their performance on the first exam indicated that they were not very adept at handling literary devices in their writing. However, as the results of the posttest demonstrate, their performances were judged to be excellent and improved as a result of attending a course that focused on using enough imagination and literary strategies in creative writing. The study's findings have shown that employing literary device techniques with diverse sorts and purposes maximizes students' capacity for short story and allegory writings.